2017
DOI: 10.1039/c7py00801e
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of anti-fouling coatings at the surface of supramolecular elastomeric materials via post-modification of reactive supramolecular additives

Abstract: Protein repellent coatings have been extensively studied to introduce anti-fouling properties at material surfaces. Here we introduce a covalent anti-fouling coating at the surface of supramolecular ureidopyrimidinone (UPy) based materials introduced via post-modification of reactive UPy-functionalized tetrazine additives incorporated into the supramolecular polymer material. After material formulation, an antifouling coating comprised of bicyclononyne (BCN) functionalized poly(ethylene glycol) (PEG) polymers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…In Pape et al no obvious difference was found between a bivalent PEG 10k diUPy and a monovalent PEG 5k diUPy in spin‐coated 2D films. In a postmodification approach however, in which molecular design has been shown to be important for functionalization efficiency, we have reported that bivalent PEG additives outperformed monovalent PEG in terms of antifouling properties when the additives were reacted to the surface using a click reaction …”
Section: Antifouling Properties Of Electrospun Scaffoldsmentioning
confidence: 99%
“…In Pape et al no obvious difference was found between a bivalent PEG 10k diUPy and a monovalent PEG 5k diUPy in spin‐coated 2D films. In a postmodification approach however, in which molecular design has been shown to be important for functionalization efficiency, we have reported that bivalent PEG additives outperformed monovalent PEG in terms of antifouling properties when the additives were reacted to the surface using a click reaction …”
Section: Antifouling Properties Of Electrospun Scaffoldsmentioning
confidence: 99%
“…Several recent studies dealing with ultra‐low fouling surface–cell interactions focused on a specific application without aiming to generalize the observed surface–cell effects 4,18–21. Some complex surface–cell relationships have been recently reported—the ultra‐low fouling surface wettability (or hydrophilicity),22,23 hydration and layer thickness,24–26 zwitterionization,27 and charge, and the presence of various functional groups28 have been shown to influence cellular behavior. The differentiation of stem cells was investigated in dependence on surface hydrophilicity and zwitterionization of the coating 29.…”
Section: Introductionmentioning
confidence: 99%
“…Further, by infusing a series of protein samples across a range of concentrations, one can obtain an adsorption isotherm and approximate a dissociation constant. Therefore, QCM is a useful tool for materials development applications (e.g., antifouling membranes, biomaterial coatings,) and a sensitive detecting element for biosensing applications (e.g., medical diagnostics).…”
Section: Introductionmentioning
confidence: 99%